2013
DOI: 10.1002/cite.201200201
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Approaches for Modeling Hydrocarbon Conversion Reactions in Zeolites

Abstract: Methodological advances in quantum chemistry and classical molecular simulation combined with the ever increasing speed of computers allow for approaching chemical accuracy in the prediction of thermodynamic and kinetic parameters of zeolite catalyzed hydrocarbon reactions. In this account, progress in the area of multiscale modeling is illustrated by two examples taken from the authors' recent work and needs for further developments are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Of course such an approach has its limits and it is obvious that future modeling techniques will have to focus more and more on a multiscale modeling approach. 12,[201][202][203][204] Still the examples shown herein already constitute a major step forwards as it has been shown that the reaction at the active site can be modelled with very good accuracy, provided the mechanism is known.…”
Section: Chemical Accuracy For Enthalpy Barriers and Kinetic Accuracy...mentioning
confidence: 79%
“…Of course such an approach has its limits and it is obvious that future modeling techniques will have to focus more and more on a multiscale modeling approach. 12,[201][202][203][204] Still the examples shown herein already constitute a major step forwards as it has been shown that the reaction at the active site can be modelled with very good accuracy, provided the mechanism is known.…”
Section: Chemical Accuracy For Enthalpy Barriers and Kinetic Accuracy...mentioning
confidence: 79%
“…In this very recent work [95], the authors have achieved chemical accuracy of ± 2 kcal/mol for predicted ethene methylation activation barriers. Other applications of such multi-scale QM/QM schemes have been reported by Hansen and Keil [97]. Although such QM/QM schemes may be too computationally expensive for routine use, they could potentially be used to benchmark more cost-effective approaches [95].…”
Section: Subtractive Schemesmentioning
confidence: 97%
“…Some interesting reviews appeared also recently on multiscale modeling of hydrocarbon conversion processes, which might be interesting for more in depth reading. 367,368 Swisher et al performed a theoretical simulation of n-alkane cracking in zeolites using an innovative combination of various theoretical methods. 369 The apparent rate constants for cracking of C3-C6 species were determined by separating the intrinsic kinetics of the alkane cracking from the thermodynamics of the adsorption step.…”
Section: Applications Using Zeolites: Selective Case Studiesmentioning
confidence: 99%